Empirically comparing the performance of blockchain's consensus algorithms. Issue 1 (13th May 2021) - Ahmad, Ashar; Alabduljabbar, Abdulrahman; Saad, Muhammad; Nyang, DaeHun; Kim, Joongheon; Mohaisen, David
Abstract: Blockchain‐based audit systems suffer from low scalability and high message complexity. The root cause of these shortcomings is the use of "Practical Byzantine Fault Tolerance" (PBFT) consensus protocol in those systems. Alternatives to PBFT have not been used in blockchain‐based audit systems due to the limited knowledge about their functional and operational requirements. Currently, no blockchain testbed supports the execution and benchmarking of different consensus protocols in a unified testing environment. This paper demonstrates building a blockchain testbed that supports the execution of five state‐of‐the‐art consensus protocols in a blockchain system; namely PBFT, Proof‐of‐Work (PoW), Proof‐of‐Stake (PoS), Proof‐of‐Elapsed Time (PoET), and Clique. Performance evaluation of those consensus algorithms is carried out using data from a real‐world audit system. These results show that the Clique protocol is best suited for blockchain‐based audit systems, based on scalability features.